PMO-162 Pregnant mothers with chronic hepatitis B (HBV): how often is treatment needed?. (28th May 2012) - Dyson, J; Michael, E; Turley, A; Moses, S; Valappil, M; Hudson, M; Bassendine, M; McPherson, S
Abstract : Introduction: HBV is a common cause of chronic liver disease worldwide. Vertical transmission is the commonest mode of infection. Since 2000 antenatal HBV screening is offered to all pregnant women in the UK. The British Viral Hepatitis Group recommend treating mothers with an HBV DNA level of >10 7 IU/ml with antivirals in the 3rd trimester to reduce the transmission risk. Few studies have evaluated the epidemiology/management of pregnant patients with HBV in the UK. We reviewed the management of mothers with HBV attending our obstetric services. Methods: Retrospective notes review of all HBV positive mothers who attended the obstetric service from January 07 to November 11. Data were collected on patient demographics, viral serology, HBV DNA and ALT levels and HBV management during their first pregnancy in the time period. Results: 81 HBsAg positive mothers (median age 28, 18–44) had 113 pregnancies in the study period. 96% were referred to the viral hepatitis service; however 28% of women did not attend >1 appointment. The mothers were born in 28 countries, most commonly China (30%) followed by countries in Eastern Europe (17%), Africa (16%), South Asia (16%) and elsewhere (21%). 29% were known to have chronic HBV (cHBV). All mothers were tested for HBeAg/Ab status: 15% were HBeAg positive, 85% HBeAg negative and 79% anti-HBe positive. 85% had HBV DNA checked during the pregnancy. 9% had active HBeAg positive cHBV (HBV DNA >20 000 IU/ml, ALT >40), 3% had active HBeAg negative cHBV (HBV DNA >2000 and ALT >40), 9% were immunotolerant (HBeAg positive, ALT <40), 60% were inactive carriers (HBV DNA <2000 and ALT <40) and 19% were indeterminate. 13% of mothers had a HBV DNA >10 7 IU/ml, but only two patients were treated with tenofovir in the 3rd trimester. Of the eight patients with active HBV, six were successfully treated post-partum with oral antivirals/PEG-Interferon and two became inactive. 20% of inactive carriers experienced a post-partum flare in ALT that settled spontaneously. Conclusion: A high proportion of HBV infected mothers were born overseas; >1 in 6 had active cHBV or HBV DNA >10 7 IU/ml and were eligible for treatment to reduce the vertical transmission risk and/or prevent disease progression. All HBV infected mothers should be assessed for treatment and efforts to improve attendance at clinic appointments need to be intensified. Competing interests: None declared.